2010
DOI: 10.1097/olq.0b013e3181b5f15d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Menses on Clearance of Y-Chromosome in Vaginal Fluid: Implications for a Biomarker of Recent Sexual Activity

Abstract: Self-reported sexual behaviors are subject to bias. We previously developed a polymerase chain reaction for the detection of Y-chromosome sequences in vaginal fluid as a potential biomarker for recent sexual activity. In this study, we found menses results in lower Y-chromosome concentrations but with similar decay patterns as non-menstrual samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…The sensitivities and concentrations that we report in this study are consistent with other studies, utilizing inoculation or timed intercourse, assessing YcDNA [16,17,26,30]. The half-life of YcDNA is estimated to be 3.6 days [16,17,26] and a previous clinical study reported that YcDNA was absent by 15 days post exposure [17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The sensitivities and concentrations that we report in this study are consistent with other studies, utilizing inoculation or timed intercourse, assessing YcDNA [16,17,26,30]. The half-life of YcDNA is estimated to be 3.6 days [16,17,26] and a previous clinical study reported that YcDNA was absent by 15 days post exposure [17].…”
Section: Discussionsupporting
confidence: 88%
“…Two genes on the Y chromosome that are of particular interest are the sex determining region of the Y chromosome (SRY) and the testis-specific protein Y-encoded 4 (TSPY4) gene [2729]. These biomarkers were utilized in small clinical trials, from the cell pellet from cervicovaginal lavage specimens [17] and vaginal swabs [5,17,26,30]. …”
Section: Introductionmentioning
confidence: 99%
“…Rapid stain identification of human semen (RSID) that detects the presence of semenogelin has also been used in trials to indicate that a woman has been exposed to ejaculate in the previous 48 hours, but is 10-fold less sensitive than quantitative PCR methods to detect Y chromosomal (Yc) DNA (12, 13). Depite heterogeneity in both initial deposit of Yc DNA and rate of decline of Yc DNA signal, Yc has the advantage of detectability up to 15 post-coital days from self-collected vaginal swabs without impact from menses on the rate of decay (14, 15). Yc DNA is not detected in women using condoms correctly as demonstrated by a study that showed that only 5/56 women had positive Yc DNA results after condom use following a 14 day abstinence period and the 5 detections were associated with receptive oral sex and digital penetration (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, biomarkers, including the detection of prostate specific antigen (PSA) and Y chromosomal (Yc) DNA in female genital tract samples, have been used as a measure of semen exposure when condomless sex occurred within the past 7 days (911). PSA degrades in 24–48 hours (10,12,13) while Yc DNA has been shown to be detectable for at least 7 days (14,15), making Yc DNA testing potentially more sensitive to detecting condomless sex and a proxy measure of recent condomless sex.…”
Section: Introductionmentioning
confidence: 99%